â€œHidupku adalah Pilihankuâ€: Penerapan Konseling Kelompok Realita untuk Meningkatkan Keterampilan Pemecahan Masalah - Imam Ariffudin (Universitas Kanjuruhan Malang, 2020)
The research aims to test the effectiveness of Reality group counseling in improving students' problem-solving skills. Quantitative research method with pretest-posttest control group design with repeated measurement model selected as the basis of research implementation. Research data is collected with problem-solving inventory and analyzed using mixed ANOVA analysis design. Statistical analysis results show that group counseling can significantly improve students' problem-solving skills. This can be due to the dynamics and climate within the counseling group, able to facilitate students to develop effective cognitive abilities and dare to deal with problems directly. Based on the results of analysis and discussion, it can be concluded that reality group counseling is effective in addressing problem-solving skills. Therefore, counselors as facilitators of student development can use this approach as an alternative to alleviating student problems in schools.